A The Analysis of Energy Efficiency and Emission Rate of a Cookware coated with Enamel Material - Pramadhony Pramadhony; Martin Luther King; Muhammad Lazim; Sukarmansah Sukarmansah; Helmi Ibrahim (Indonesian Journal of Environmental Management and Sustainability, 2019)
Metal cookware has been used many people for its better thermal conductivity. However this material also has some weaknesses for its reaction with acidic food which will contaminate the food. Metal-base material coated with enamel is one of the solutions. The hard and non-reactive surface has cause this material has been widely used for processing food. Lower thermal conductivity is one of the problems of enamel cookware. The experimental analysis has been conducted to investigate energy efficiency, emission rate and thermal conductivity. The efficiency is calculated by comparing the useful energy (work) with the input energy. The emission rate is calculated by multiply energy consumption with emission factor. Meanwhile the thermal conductivity is calculated by using simply conduction heat transfer equation. Based on the analysis, enamel cookware has much lower thermal conductivity than aluminum cookware. However this physical property does not much affects the efficiency. The most dominant factors which should considered are type of fuel and technology of stove which consume higher energy inefficiently and emits much higher hazardous gas